The court and the constitution of India summits and shallows - Chinnappa Reddy, O. (New Delhi ; Oxford : Oxford University Press, 2008)
This narrative of the working of the Indian Supreme Court enables us to assess its collective strength and fragility as an institution of national governance, and guides us through the maze of constitutional interpretation created by India's most eminent justices. It contributes towards civic and republican education about the role of summit justices in a rapidly changing post-colonial, and now also hyperglobalizing, India.
Includes bibliographical references and indexes.
Description based on print version record.
Keywords: Judicial power -- India; India. -- Supreme Court; India; Courts -- India; Justice, Administration of -- India